Legal mentality and rulemaking - Bakirov Д.А.; Zhusipov А.Д. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
Effective functioning of all elements is essential for the legal system. The legal system is the most complex form of a system aimed at achieving a certain goal and is a system capable of changing its own structure in the process of working. Studying the peculiarities of the legal mentality of society and individuals, the need to study norm-making contributes to raising the level of legal consciousness and legal culture in Kazakhstan society to a new level. This is one of the important areas of national legal science. Access to public information and participation in the development of drafts of normative legal acts affecting the interests of citizens is an important means of improving the legal system of the "information society". Access to information allows citizens to control the activities of authorities, thereby preventing legal arbitrariness. In this context, it is important to form a position of active participation of citizens in electronic norm-making activity. The article deals with the issues of participation of citizens in rule-making activities and formation of legal mentality in Kazakhstani society. The result of the study is the analysis of the current state of the national legal system, the development of legal culture, legal consciousness and legal mentality from today’s point of view, the development of directions and measures for deep understanding.